2015
DOI: 10.7863/ultra.14.12006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Abdominal Muscle Thickness and Maximal Expiratory Pressure

Abstract: Our results indicate that the rectus abdominis muscle thickness might be more highly correlated with expiratory pressure production than the external oblique, internal oblique, and transverse abdominis muscle thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…33 The thickness of the rectus abdominis among different groups has been evaluated with various methods (Supplement Table 4, http:// links.lww.com/EJA/A445). 8,12,[33][34][35][36] In our study, neither the thickness of the rectus abdominis nor the BMI alone was associated with outcomes. Tandon et al 37 reported that combining BMI and thigh muscle thickness measured by ultrasound can identify patients with sarcopenia.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…33 The thickness of the rectus abdominis among different groups has been evaluated with various methods (Supplement Table 4, http:// links.lww.com/EJA/A445). 8,12,[33][34][35][36] In our study, neither the thickness of the rectus abdominis nor the BMI alone was associated with outcomes. Tandon et al 37 reported that combining BMI and thigh muscle thickness measured by ultrasound can identify patients with sarcopenia.…”
Section: Discussioncontrasting
confidence: 76%
“…Site-specific sarcopenia may be present before wholebody sarcopenia. 15,33 Ishida et al 34 reported that the thickness of the rectus abdominis correlated better with expiratory pressure production than with thickness of other abdominal muscles. 33 The thickness of the rectus abdominis among different groups has been evaluated with various methods (Supplement Table 4, http:// links.lww.com/EJA/A445).…”
Section: Discussionmentioning
confidence: 99%
“…However, it was observed that subjects with GJH had lower values in maneuvers requiring forced expiration such as FEV1 and MEP. This suggests that the abdominal muscles, which play an important role in forced expiration, may also be affected due to deterioration in the connective tissue (37,38). Studies in the literature on functional muscle strength in joint hypermobility generally focus on the lower extremity muscles, but more research is required to investigate trunk muscles including abdominals.…”
Section: Discussionmentioning
confidence: 99%
“…The remarkable finding was that as the inward pressure increased, the ICC values of muscle thickness improved. To obtain a stable position, orientation, and consistent inward pressure of the transducer, delicate attention is required during rehabilitative ultrasound imaging [24]. When specific inward pressure is applied, vibration and the gap between the gel and skin might be minimized.…”
Section: Discussionmentioning
confidence: 99%